PERANAN ADVOKAT DALAM MEMBERIKAN JASA HUKUM DEMI TEGAKNYA SUPREMASI HUKUM - Lubis, Fauziah; Lubis, Hidayatus Saadah; Nasa, Raihan; Harahap, Irham Rosidi; Ihsan, Ibnu; Siregar, Harun Al Rasyid Firdaus (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
The principle of the rule of law demands a guarantee of equality for everyone before the law (equality before the law). The Constitution also stipulates that everyone has the right to recognition, guarantee, protection and legal certainty in community and state life, the role and function of advocates as a free, independent and responsible profession is important, in addition to judicial institutions and law enforcement agencies. The role of advocates here is how advocates can carry out their profession in accordance with their duties and functions and in accordance with the code of ethics and oath taken by advocates is to accompany, become legal counsel, provide legal services to clients, both socially and on the basis of receiving honorariums. The purpose of this study is to find out how advocates carry out their duties and professions for the sake of upholding justice based on law for people seeking justice before the law. The research method used is normative with an empirical legal approach using theories and concepts to examine legislation. Advocates in carrying out their duties and functions accompany suspects/defendants in criminal cases and plaintiffs/defendants in civil cases in carrying out their defense when facing a case